2022
DOI: 10.1001/jama.2022.2017
|View full text |Cite
|
Sign up to set email alerts
|

Association of COVID-19 Acute Respiratory Distress Syndrome With Symptoms of Posttraumatic Stress Disorder in Family Members After ICU Discharge

Abstract: IMPORTANCE Persistent physical and mental disorders are frequent in survivors of COVID-19-related acute respiratory distress syndrome (ARDS). However, data on these disorders among family members are scarce.OBJECTIVE To determine the association between patient hospitalization for COVID-19 ARDS vs ARDS from other causes and the risk of posttraumatic stress disorder (PTSD)-related symptoms in family members. DESIGN, SETTING, AND PARTICIPANTS Prospective cohort study in 23 intensive care units (ICUs) in France (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
70
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 33 publications
5
70
0
5
Order By: Relevance
“… 13 Post-traumatic stress disorder (PTSD) has been reported in 35% of caregivers and independently associated with COVID-19-related ARDS. 14 Younger children are rarely studied but are at considerable risk for PTSD. 15 COVID-19 illness was often clustered within families, leading to multiple family members in hospital or the ICU simultaneously.…”
mentioning
confidence: 99%
“… 13 Post-traumatic stress disorder (PTSD) has been reported in 35% of caregivers and independently associated with COVID-19-related ARDS. 14 Younger children are rarely studied but are at considerable risk for PTSD. 15 COVID-19 illness was often clustered within families, leading to multiple family members in hospital or the ICU simultaneously.…”
mentioning
confidence: 99%
“…Restoring speech has long been a priority for patients with tracheostomy [45] , [46] , but placement of one-way valves and decannulation were often delayed during the pandemic. The vulnerability inherent in relying on others for care also may have increased anxiety, as impaired communication in this population increases anxiety, depression, and stress for both HCP and patients [47] . Few studies have specifically explored patients and families' survivorship challenges [48] which can affect mental health, physical impairments, and cognitive impairments.…”
Section: Discussionmentioning
confidence: 99%
“…In a population-based cohort of spouses of critically ill patients with sepsis and septic shock, the incidence of new mental illness among spouses was 23.5%, which was in excess of the general population during the same time period [ 11 ]. Finally, very recent prospective data from France showed that caregivers of patients with acute respiratory distress syndrome (ARDS) secondary to coronavirus disease 2019 (COVID-19) had higher incidence of PTSD symptoms compared to not only the general public, but caregivers of patients with ARDS from other causes [ 12 ]. This underscores the role of the pandemic, which has clearly heightened concerns of post-discharge mental health morbidity among ICU survivors and their caregivers.…”
Section: Mental Health Morbidity Among Caregiversmentioning
confidence: 99%